OVERCOMING LINGUISTIC AND DIDACTIC DIFFICULTIES IN THE STUDY OF A FOREIGN LANGUAGE AS A MEANS OF FORMATION COGNITIVE INDEPENDENCE OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS AND ACCREDITATION LEVELS (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the problem concerning linguistic and didactic difficult foreing language studies and the ways og their overcoming as the means of students'  independence forming in higher educational establishments of the I-II sccreditation levels.
Keywords: linguistic and didactic difficulties; cognitive independence; higher educational establishments of the I-II sccredition levels